2007
DOI: 10.1167/iovs.06-0845
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Oscillatory Potentials and Photopic Negative Response in Patients with Autosomal Dominant Optic Atrophy withOPA1Mutations

Abstract: These results suggested that there are functional impairments not only in the ganglion cell layer but also in the inner nuclear and plexiform layers, including the amacrine cells of ADOA patients with OPA1 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 30 publications
2
52
0
1
Order By: Relevance
“…12,15 PhNR is also selectively reduced in eyes with optic nerve atrophy, which is induced by trauma, compression, inflammation, ischemia, or gene mutation. [8][9][10] Our results provide additional evidence that focal macular PhNR is immediately and strongly attenuated by the onset of optic neuritis and that PhNR did not improve even after patients were treated with systemic corticosteroids, which resulted to improved visual acuity and visual field but not optic atrophy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…12,15 PhNR is also selectively reduced in eyes with optic nerve atrophy, which is induced by trauma, compression, inflammation, ischemia, or gene mutation. [8][9][10] Our results provide additional evidence that focal macular PhNR is immediately and strongly attenuated by the onset of optic neuritis and that PhNR did not improve even after patients were treated with systemic corticosteroids, which resulted to improved visual acuity and visual field but not optic atrophy.…”
Section: Discussionmentioning
confidence: 61%
“…[1][2][3][4][5][6][7][8][9] In clinical studies using full-field ERGs, the PhNR amplitude was reduced in various diseases that involves RGC damageFfor example, glaucoma, [3][4][5] retinal vascular disease, 6,7 and optic nerve diseases. [8][9][10] Several researchers measured PhNR by using focal macular ERG in humans and monkeys. [11][12][13][14][15] Focal macular PhNR detected early glaucoma with higher sensitivity and specificity than full-field PhNR.…”
Section: Introductionmentioning
confidence: 99%
“…9,31 In addition, the electroretinograms in patients with ADOA are, in general, normal. 1,[41][42][43] Thus, the photoreceptor layer is most likely not affected in this disease. The overall sensory retinal thickness at the fovea was normal in patients with ADOA probably because the RNFL and ganglion cell layer are essentially absent in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the ERG obtained in response to a long-duration red flash of moderate intensity provides optimal delineation of the PhNR ON and PhNR OFF components. 23,26,27 The brief-flash PhNR is attenuated in patients with ADOA 28 and in the Opa1 Q285STOP mutant mouse. 29 In the mouse model, the defect is seen before any changes in visual acuity on optokinetic drum testing and before morphologic changes on retinal histology.…”
Section: Purposementioning
confidence: 99%
“…Miyata et al 28 and Barnard et al 29 highlight the diagnostic potential of the PhNR in ADOA; however, the investigators used a brief white flash (broadband stimulus) to evoke the PhNR, which provides a poor signal-to-noise ratio compared with monochromatic stimuli, 26 and cannot distinguish ON and OFF components. Furthermore, the studies elicited full-field (global) PhNRs that, in contrast to the focal PhNR, are less sensitive in detecting focal retinal lesions, such as those seen in early to moderate glaucoma.…”
Section: Purposementioning
confidence: 99%